2003
DOI: 10.1089/152702903322022794
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Llama versus the Fetal Sheep: Different Strategies to Withstand Hypoxia

Abstract: The pregnant llama (Lama glama) has walked for millions of years through the thin oxygen trail of the Andean altiplano. We hypothesize that a pool of genes has been selected in the llama that express efficient mechanisms to withstand this low-oxygen milieu. The llama fetus responds to acute hypoxia with an intense peripheral vasoconstriction that is not affected by bilateral section of the carotid sinus nerves. Moreover, the increase in fetal plasma concentrations of vasoconstrictor hormones, such as catechola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…Despite an assumingly lower NOmediated vasorelaxation in the chronic hypoxic chicken embryo due to impaired endothelial function, we still observe a hypotensive response to chronic hypoxia. We have previously shown that the CAM vasculature is not innervated, i.e., is not subject to cholinergic stimulation of NO release (in fact, exogenous ACh does not relax, but constricts, CA arteries) (27). Additionally, we report here that the femoral arteries from hypoxic chicken embryos show an increased sensitivity to ␤AR-mediated relaxation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Despite an assumingly lower NOmediated vasorelaxation in the chronic hypoxic chicken embryo due to impaired endothelial function, we still observe a hypotensive response to chronic hypoxia. We have previously shown that the CAM vasculature is not innervated, i.e., is not subject to cholinergic stimulation of NO release (in fact, exogenous ACh does not relax, but constricts, CA arteries) (27). Additionally, we report here that the femoral arteries from hypoxic chicken embryos show an increased sensitivity to ␤AR-mediated relaxation.…”
Section: Discussionmentioning
confidence: 51%
“…1), yet hypotension remained. In the absence of a chemoreflex, cardiovascular function in the chicken embryo is mainly maintained through adrenergic pathways stimulated by catecholamines of adrenomedullary rather than sympathetic origin (11), which, in turn, could elevate heart rate as shown in the chronically hypoxic sheep fetus (14,27). Circulating norepinephrine levels are increased in E19 chickens (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…During high-altitude LTH, the CBF in adult humans (23,60) and sheep (34,63) returns to normal following a period of transitional increased blood flow, as compiled by Brugniaux et al (8). The ovine near-term fetus diverts an increased fraction of total cardiac output to the brain, when subjected to hypoxia during gestation.…”
mentioning
confidence: 92%
“…Some chickens found on the Peruvian Altiplano show a mutant hemoglobin with a high affinity for O 2 when compared to their sea level cousins (Mejia et al 1994). Adaptation can also be seen at the embryo level: the permeability of the egg shell of some high altitude birds is higher than the similar species living at sea level (Leon-Velarde et al 1997), cerebral blood flow of the llama's fetus does not increase in hypoxia, as opposed to what happens in sea level sheep (Llanos et al 2003). Further investigations in humans and animal species adapted to high altitude will be necessary to better understand how living organisms cope with hypoxia, using so various strategies.…”
Section: Example: Life At High Altitudementioning
confidence: 99%